2014
DOI: 10.1021/cg501277d
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization in Ionic Liquids: Synthesis, Properties, and Polymorphs of Uranyl Salts

Abstract: Crystallizations in uranyl-containing ionic liquids yielding crystals {X} a {[UO 2 ] b [Y] c } with selected anions and cations (X = [Bmim] + for Y = Cl − , NO 3 − , and SCN − ; Y = Cl − for X = [Emim] + , [Emmim] + , [Bmim] + , and [Bmmim] + ;Emim = l-ethyl-3-methyl-imidazolium, Emmim = l-ethyl-2,3-dimethylimidazolium, Bmim = l-butyl-3-methylimidazolium, and Bmmim = l-butyl-2,3-dimethylimidazolium) were performed herein. Through standard crystallographic analyses, Hirshfeld surface analyses, and multiple char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 102 publications
0
18
0
Order By: Relevance
“…Schnaars and Wilson [125] hypothesized that the 15 cm −1 difference in the symmetric stretching band arose from either 1) additional hydrogen bonding to the uranyl oxo in the monoclinic form or 2) subtle differences in the UACl bond lengths that would lead to an increased electrostatic effect and uranyl bond destabilization. Qu et al demonstrated similar effects by crystallizing the uranyl tetrachloro species with imidazolium cations [126]. An 8 cm −1 difference was observed between [Emim] 2 UO 2 Cl 4 (Emim = 1-ethyl-3-methyl-imidazolium; 827 cm −1 ) and [Emmim] 2 UO 2 Cl 4 (Emmim = 1-ethyl-2,3-dimethylimidazolium; 835 cm −1 ).…”
Section: Chemical and Structural Elucidation Of Uranium Solid-state Cmentioning
confidence: 86%
“…Schnaars and Wilson [125] hypothesized that the 15 cm −1 difference in the symmetric stretching band arose from either 1) additional hydrogen bonding to the uranyl oxo in the monoclinic form or 2) subtle differences in the UACl bond lengths that would lead to an increased electrostatic effect and uranyl bond destabilization. Qu et al demonstrated similar effects by crystallizing the uranyl tetrachloro species with imidazolium cations [126]. An 8 cm −1 difference was observed between [Emim] 2 UO 2 Cl 4 (Emim = 1-ethyl-3-methyl-imidazolium; 827 cm −1 ) and [Emmim] 2 UO 2 Cl 4 (Emmim = 1-ethyl-2,3-dimethylimidazolium; 835 cm −1 ).…”
Section: Chemical and Structural Elucidation Of Uranium Solid-state Cmentioning
confidence: 86%
“…There is no information available on the presence of such complexes in the pure inorganic systems. Another distinctive feature of this topology is that the common edge between Ur hexagonal bipyramids is commonly performed by the OH groups (e.g., [32,33]), while lower amount of structures hydroxyl groups are replaced by H 2 O molecules (e.g., [34,35]).…”
Section: Structural Topologymentioning
confidence: 99%
“…The constituents of some ILs have ligand binding characteristics. Engineering CPs with ILs expands the range of functional properties that may be readily accessed for emergent applications [8–10] . The negligible volatility of ILs can make it challenging to use solvent evaporation strategies to synthesize IL‐containing CPs.…”
Section: Introductionmentioning
confidence: 99%
“…Engineering CPs with ILs expands the range of functional properties that may be readily accessed for emergent applications. [8][9][10] The negligible volatility of ILs can make it challenging to use solvent evaporation strategies to synthesize IL-containing CPs. The solvation capacity of certain ILs for metal salts would require the development of strategies to force CP precipitation from the stable metal salt-IL solution.…”
Section: Introductionmentioning
confidence: 99%